Design of Control System of Electric Executer of Hydro-valve Based on STC89C51 - CAO Jing-long; AN Bai-xiu; NIU Jie (Gong-kuang zidonghua, 2011)
The paper introduced structure and working principle of an electric executer of hydro-valve based on STC89C51 single-chip microcomputer and expounded composition and design schemes of software and hardware of control system of the electric executer. The control system takes STC89C51 single-chip microcomputer as core, uses ring distributor and power amplifier to control rotator speed and rotator angle of step motor so as to control opening degree of the hydro-valve, and adopts a flow sensor and a pressure sensor to collect hydro-parameter signals, which are sent to STC89C51 single chip microcomputer after AD conversion so as to form closed loop control. The control system has functions of CAN communication and human-machine interaction.